Ecophysiological and behavioral determinants of niche range in hibernating bats affected by white nose syndrome - Golas, Benjamin D., author; Webb, Colleen, advisor; Cryan, Paul, committee member; Hayman, David, committee member; Huyvaert, Kathryn, committee member (Colorado State University. Libraries, 2022)
The restrictions of a fundamental niche range, physiological conditions under which an organism can persist, becomes increasingly important as populations are subjected to extreme climatic conditions. Hibernating animals are annually subjected to such extremes. For example, insectivorous bats will survive months without caloric intake in winter by lowering body temperature to near freezing to mitigate loss of energy through heat transfer and water through evaporation. However, there is strong overlap between the fundamental niche of hibernating bats and that of the keratinolytic fungus, Pseudogymnoascus destructans (Pd). As a result of Pd growth disrupting wing membranes, hibernating bats are forced to enact frequent energetically costly arousals that can result in starvation and mortality. The resulting disease, white nose syndrome (WNS), has resulted in mass die offs of millions of hibernating bats across North America since Pd introduction. However, there is significant inter- and intraspecific variation in host responses, and the realized niche for bat hibernation may be wider and more variable than previously theorized, making host responses difficult to predict. Ecophysiological models predict torpor arousal and hibernation survival with WNS as a function of microclimates, but they are largely dependent on laboratory-based experiments measuring metabolic parameters like metabolic rate and evaporative water loss that are likely subject to intraspecific local variation. We require a better understanding of the physiological, environmental, and behavioral drivers of successful bat hibernation in natural systems with and without Pd so we can improve risk assessment and guide management strategies for populations affected by WNS. To better understand how torpor arousal is dependent on experienced microclimates, we attached temperature and humidity data loggers to free-ranging Eptesicus fuscus to record microclimates and arousal frequency throughout hibernation. Fitting this data to ecophysiological models describing torpor, we found that while ecophysiological models provide adequate boundaries to biological capabilities for arousal, stochasticity inherent in natural systems can lead to earlier and more frequent arousal than models suggest. To determine how hibernation roosting niche is constrained in spatiotemporally variable hibernacula, we measured microclimates throughout a hibernaculum where Myotis lucifugus populations have thrived despite regional WNS-related mass mortality. Using hierarchical modeling to predict spatiotemporal underground microclimates based on above-ground conditions, we find that hibernation roosts are likely established early in the hibernation season at microsites that are locally stable within a given hibernaculum chamber, but not necessarily the most stable across the hibernaculum. This suggests that M. lucifugus are capable of a more flexible niche space than previously theorized, which may assist in WNS survival. Lastly, we use approximate Bayesian computation to test different hypotheses for how bats survive WNS in this hibernaculum, using ecophysiological models and longitudinal microclimate data to compare local adaptation, microclimate selection, clustering, and grooming strategies. While grooming removal of Pd load appears to be essential to describe observed population survival, we find evidence of all four hypotheses contributing to biologically realistic survival. Ultimately, the indirect fundamental niche range contraction due to Pd disrupting physiological host processes is mitigated by a combination of adaptation and conspecific facilitation expanding realized niche range. Our work represents advancements in novel technological and modeling advancements that allow evaluation of niche range in free-living populations. The results of this study suggest that there are populations with exaptations that facilitate WNS survival, but that alteration of environmental conditions in other hibernacula could lead to a change in niche space outside the range for which residents are locally adapted. Our findings help to inform and guide assessment of at-risk species and inform potential management strategies by considering the significant individual- and population-level variation in local adaptation and microclimate use that can impact WNS survival.
Keywords: disease; niche; white nose syndrome; hibernation; bats; torpor